150 Impact of Behavioral Disorders and their Pharmacological Treatment on the Maturational Trajectories of NREM Slow Wave Activity. (3rd May 2021) - Fernandez-Mendoza, Julio; Ricci, Anna; He, Fan; Fang, Jidong; Calhoun, Susan; Cain, Patricia; Vgontzas, Alexandros; Liao, Duanping; Bixler, Edward
Abstract: Introduction: Slow wave activity (SWA) in the delta (0.4-4 Hz) frequency range declines in typically developing (TD) children as they transition to adolescence. However, it remains unknown whether the maturational trajectory of NREM delta power differs between TD youth and those with psychiatric/behavioral disorders. Methods: We analyzed the sleep EEG of 664 subjects aged 6 to 21 (46.8% female, 24.7% racial/ethnic minority) from the Penn State Child Cohort, of whom 449 were TD, 123 were un-medicated and diagnosed with psychiatric/behavioral disorders, and 92 were medicated with stimulants, anti-depressants, anxiolytics, sedatives and/or anti-psychotics. Multivariable regression models adjusting for sex, race/ethnicity, BMI, AHI and PSG system tested the age-related trajectories of NREM delta power within each diagnostic group. Results: Delta power in TD and un-medicated youth showed cubic age-related trajectories (both p-cubic<0.05). In TD youth, delta power was highest at age 6.6 and lowest at age 19.9, while in un-medicated youth it was highest at age 8.9 and lowest at age 18.6. The decreasing slope in delta power was 39.7% steeper in un-medicated youth (-22422 ± 5891/year, p<0.01) than TD youth (-16047 ± 2605/year, p<0.01). Delta power in medicated youth showed a distinct linearly decreasing trajectory (-13518 ± 4597/year, p-linear<0.01) from age 6 (highest) to age 21 (lowest). Conclusion: TD and un-medicated youth with psychiatric/behavioral disorders show SWA trajectories typical of brain maturation biomarkers (e.g., gray matter volume), characterized by a decreasing slope at the onset of puberty that reaches its nadir by late adolescence. However, SWA in un-medicated youth peaks two years later and reaches its nadir a year earlier than in TD youth. Thus, while TD children experience a smooth decline in SWA in the transition to adolescence, those with psychiatric/behavioral disorders experience a faster steep decline. In contrast, SWA in medicated youth appears to be dampened in early childhood and its slope linearly decreases with age. These data suggest that these youth may have a more severe disorder requiring pharmacological treatment, that the latter produces greater cortical arousability reflected in lower SWA power, and/or that psychoactive medications directly impact normal neurodevelopmental processes (e.g., synaptic pruning). Support (if any): NIH Awards Number R01MH118308, R01HL136587, R01HL97165, R01HL63772, UL1TR000127